ELAZIĞ İL MÜFTÜLÜĞÜ’NÜN HİZMETLERİNE SOSYOLOJİK BİR BAKIŞ [47-73] - Güneş, Abdurrahman (Fırat University, 2015)
İnsanların yaratılışında bir şeye inanma ve sığınma duygusu bulunmaktadır. Bu durum bireyleri inanç ve din fikrine götürmektedir. Her toplumda mutlaka bir din olgusunun var olduğu sosyolojik bir gerçeklik olarak kabul edilmektedir. Bu gerçeklik, tarihin hiçbir döneminde değişmemiştir. Günümüzde formel anlamda din hizmeti sunmaya çalışan kurum, Diyanet İşleri Başkanlığı?dır. Bu kurum özellikle son yıllarda yurtiçi ve yurtdışında hizmet ağını genişleterek sürdürmektedir. Camilerde her yaş gurubundan oluşan büyük bir kitleye din hizmeti sunarken cami dışında da birçok etkinlikte etkin bir rol oynamaktadır. Bu araştırmada Diyanet İşleri Başkanlığı?nın taşra teşkilatı olan Elazığ İl Müftülüğü?nün yürüttüğü dini faaliyetler tasvir edilmeye ve sosyolojik olarak yorumlanmaya çalışılmaktadır

Humans, by nature, have the need to believe in and take refuge in another being. This is what leads people to belief and the idea of religion. It is accepted as a sociological reality that there is the phenomenon of religion in every society. This reality has never changed in any period of history. In our day, Religious Affairs is the office that seeks to give religious services in formal sense. This institution has especially been operating and widespreading its services both at home and abroad for the past few years. While providing services to broad communities of all ages in mosques they have also been engaging in various public activities outside the mosques. In this study, we tried to describe the religious activities of the Religious Affairs of Elazığ and commentate them in a sociological perspective
A Sociologıcal Approach to The Services of Elazig Provincial Religious Affairs